2021
DOI: 10.1007/s00520-021-06312-8
|View full text |Cite
|
Sign up to set email alerts
|

Reporting in rodent models of ‘chemobrain’: a systematic review assessing compliance with the ARRIVE guidelines

Abstract: Reporting in rodent models of 'chemobrain': a systematic review assessing compliance with the ARRIVE guidelines

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…The occurrence of ≥ grade 1 confusion was 5% for patients aged under 65 years and 13.6% for patients aged 65 years and over (p = 0.17). Chemotherapy-induced cognitive impairment (chemobrain) could also explain this increased confusion from SRT2, although it was not representative in our series [33].…”
Section: Discussionmentioning
confidence: 67%
“…The occurrence of ≥ grade 1 confusion was 5% for patients aged under 65 years and 13.6% for patients aged 65 years and over (p = 0.17). Chemotherapy-induced cognitive impairment (chemobrain) could also explain this increased confusion from SRT2, although it was not representative in our series [33].…”
Section: Discussionmentioning
confidence: 67%
“…The occurrence of ≥ grade one confusion was 5% for patients aged under 65 years and 13.6% for patients aged 65 years and over (p = 0.17). Chemotherapy-induced cognitive impairment (chemobrain) could also explain this increased confusion from SRT2, although it was not representative in our series [ 38 ]. A prospective study would certainly have allowed us to better distinguish the toxicity related to SRT itself from that of systemic treatments and to better take into account the effect of corticosteroid therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Thus this should be considered when interpreting the preclinical results reported in the present systematic review. The observed limitations in animal studies have been identified, highlighted, and reported in multiple systematic reviews ( 229 231 ). This has led to journals requiring the use of reporting guidelines, such as the ARRIVE (Animal Research: Reporting of In Vivo Experiments) guidelines.…”
Section: Discussionmentioning
confidence: 99%